How Do Learners Observe and Assess Geography Textbook Spreads? - Behnke, Yvonne (Journal of Geography Education, 2016)
This paper investigates what degree of visual attention learners pay to design components of geography textbooks, such as photos, graphics and text, how learners assess the visual quality of their textbooks, and how the design of current geography textbooks may influence learners visual attention. In an exploratory eye tracking study using random sampling, the eye movements of 20 students (secondary school students 15–17 years of age and university students 20–24 years of age) were recorded. Double-page spreads of current German geography textbooks covering an identical topic and taken from five separate textbooks were utilised, and a two-stage test was developed. Participants first looked at the entire textbook spread to determine what was being explained on the pages, and then solved one of the tasks from the exercise section. Each participant studied five different textbook spreads and completed five set tasks. Participants subsequently completed a questionnaire. The study revealed that visuals were often looked at rather superficially. While solving the tasks, a marked focus on text was observed. Based on the observation, I describe learning-related challenges posed by components of textbook design and relate the findings to educational psychology insights and findings from visual communication and textbook analysis.